Pore Strategy Design of a Novel NiTi-Nb Biomedical Porous Scaffold Based on a Triply Periodic Minimal Surface - Lv, Yuting; Liu, Guohao; Wang, Binghao; Tang, Yujin; Lin, Zhengjie; Liu, Jia; Wei, Guijiang; Wang, Liqiang (Frontiers in Bioengineering and Biotechnology, 2022)
The pore strategy is one of the important factor affecting the biomedical porous scaffold at the same porosity. In this work, porous scaffolds were designed based on triply periodic minimal surfaces structure (TPMS) under the same porosity and different pore strategies (pore size and size continuous gradient distribution), and were successfully prepared using a novel Ni46.5Ti44.5Nb9 alloy and selective laser melting (SLM) technology. After that, the effects of the pore strategies on the microstructure, mechanical properties and permeability of porous scaffolds were systematically investigated. The results show that the Ni46.5Ti44.5Nb9 scaffolds have a low elastic modulus (0.80-1.05 GPa) and a high ductility (15.3-19.1%) compared with previous works. The pore size has little effect on their mechanical properties, but increasing the pore size significantly improves the permeability due to the decrease of specific surface. The continuous gradient distribution of the pore size changes the material distribution of the scaffold and the smaller porosity structure has a better load-bearing capacity and make the main contribution to the high compression strength. The local high porosity structure bear more fluid flow, which can improve the permeability of the overall scaffold. This work can provide theoretical guidance for the design of porous scaffolds.